Influence Of Temperature On Changes In Ph Of Appreting Solutions In The Presence Of Various Catalysts (Texas Journal of Multidisciplinary Studies, 2024)
The correct choice of catalyst, its concentration, nature and its activity in cross-linking reactions of cellulose molecules play a decisive role in the quality finishing of fabrics.